2013
DOI: 10.1098/rspb.2013.1506
|View full text |Cite
|
Sign up to set email alerts
|

Forest corridors maintain historical gene flow in a tiger metapopulation in the highlands of central India

Abstract: Understanding the patterns of gene flow of an endangered species metapopulation occupying a fragmented habitat is crucial for landscape-level conservation planning and devising effective conservation strategies. Tigers (Panthera tigris) are globally endangered and their populations are highly fragmented and exist in a few isolated metapopulations across their range. We used multi-locus genotypic data from 273 individual tigers (Panthera tigris tigris) from four tiger populations of the Satpura-Maikal landscape… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
83
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 97 publications
(98 citation statements)
references
References 67 publications
(90 reference statements)
6
83
2
Order By: Relevance
“…The number of alleles per locus at the polymorphic loci (n = 16) ranged from three to five (average 3.625), the effective number of alleles per locus ranged from 2.000 to 3.447 (average 2.781), and the mean PIC was 0.575 (Table 2). Considering the small number of individuals in our study, we support our results by examining the mean values of H E and H O (0.675 and 0.668, respectively) of the combined panel (n=16), which are comparable with the reported mean values of H E (0.655 to 0.810) and H O (0.650 to 0.7624) in non-invasive genetic studies carried out on the Bengal tiger (Reddy et al, 2012;Gour et al, 2013;Sharma et al, 2013). We established the relatedness among the captive tigers (n = 8) using the combined panel of highly polymorphic loci and estimated the mean value of the relatedness coefficient (R = -0.143), which indicated that the selected tigers were not highly related to each other, as is mostly expected in captive individuals.…”
Section: Resultssupporting
confidence: 78%
“…The number of alleles per locus at the polymorphic loci (n = 16) ranged from three to five (average 3.625), the effective number of alleles per locus ranged from 2.000 to 3.447 (average 2.781), and the mean PIC was 0.575 (Table 2). Considering the small number of individuals in our study, we support our results by examining the mean values of H E and H O (0.675 and 0.668, respectively) of the combined panel (n=16), which are comparable with the reported mean values of H E (0.655 to 0.810) and H O (0.650 to 0.7624) in non-invasive genetic studies carried out on the Bengal tiger (Reddy et al, 2012;Gour et al, 2013;Sharma et al, 2013). We established the relatedness among the captive tigers (n = 8) using the combined panel of highly polymorphic loci and estimated the mean value of the relatedness coefficient (R = -0.143), which indicated that the selected tigers were not highly related to each other, as is mostly expected in captive individuals.…”
Section: Resultssupporting
confidence: 78%
“…Over the last 300 years, the highlands lost 78 % of forest cover to agriculture and urbanization. In the past few decades, the rate at which the human footprint expanded is unparalleled (Sharma et al 2013b). Yet, this is a global priority TCL (Dinerstein et al 2007).…”
Section: Ecological Conditions In the Central Indian Highlands Are Womentioning
confidence: 98%
“…However, there has been a 47-70 % reduction in effective dispersal events (first-and second-generation migrants) between the Kanha-Pench source populations and the other tiger reserves such as Kanha-Melghat, Kanha-Satpura, and Pench-Melghat which are connected by agricultural areas and degraded forest corridors. Aside from the KanhaPench connection, other tiger reserves still connected through forest corridors-Satpura-Melghat, SatpuraPench-showed no significant change in gene flow (Sharma et al 2013b).…”
Section: Gene Flow In Central Indian Tigersmentioning
confidence: 99%
“…Kanha also serves as a source site for tiger and leopard populations throughout the central Indian landscape Sharma et al 2013) and is thus a priority region for minimizing human-carnivore conflict. In Kanha, tigers and leopards mainly kill cattle (Bos indicus), buffalo (Bubalus bubalis), and goats (Capra aegagrus hircus; Negi and Shukla 2010).…”
Section: Introductionmentioning
confidence: 99%